A Study on The Distinction between Extrovert Vs Introvert in Learning English - Hayati, Fitri Mauliddiyah (Universitas Islam Negeri Raden Intan Lampung, 2021)
This paper aims to examine the differences abilities between extrovert and introvert personality in learning English. This study describes the differences in the ability of speaking, writing, listening and reading. The approach used in this study is a qualitative approach. Data were obtained by conducting observations and interviews with research subjects. The subjects of this study were students of the third semester of English Education at IAIN Pekalongan. The analysis in this study uses a descriptive analysis related to the differences in English skills in extroverts and introverts. The results showed that the differences between extroverted and introverted personalities on the ability to learn English. In speaking skills, extroverted students are more mastery than introverted students. While writing, listening, and reading skills introverted students are more mastered. But in the aspect of pronunciation & accent, extroverts' vocabulary and fluency are superior than introverts. Introverts good in grammar, and comprehension. On the other hand, introverts have superior writing skills in terms of vocabulary, content, and expression. whereas extroverts only excel in terms of content and expression. The spelling and grammar is not influenced by the personality.Therefore each personality have own skills or advantages and disadvantages.